PENGARUH KEKERAPAN MEMBACA SURAT KABAR TERHADAP KEMAMPUAN MEMAHAMI WACANA - Golda Mair (Universitas Negeri Medan, 2014)
ABSTRACTThis study aims to determine the frequency of reading the newspaper, the ability to understand the discourse and influence the frequency of reading a newspaper on the ability to understand the discourse. The population in this study were students of class X SMA Methodist 8 Medan Year 2009/2010 Learning totaling 110 people. Samples were taken 30 people.The method used in this research is descriptive method. Data collection tool used questionnaires and tests. The questionnaire used to collect the data frequency of reading newspapers and essaytests used to collect data is the ability to understand the discourse.Once the data is collected and analyzed the results of the study showed that the statesIncidence Reading Newspaper Methodist High School Class X 8 Medan Year 2009/2010Learning is at sufficient levels to an average value of 65, Ability Discourse UnderstandingMethodist High School Class X 8 field of Learning 2009/2010 are at a high level with an average value of 68.5, and the Effect Frequency Reading the news letter to the ability ofDiscourse Understanding Class X 8 Terrain Methodist high School Year 2009/2010 are learningat a very strong level is 0.857.To test the hypothesis, used product moment correlation formula is 0.857 Furthermore,in consultation with the db table r N-2 (30-2) = 28, r = db table for 28 is 0.374. Thus rh  rt(0.857> 0.374), determination index obtained from the calculation is 73.44%. So the influence ofthe frequency of reading the newspaper with the ability to understand the discourse of class X SMA Methodist 8 Medan Year 2009/2010 Study of 73.44% means that the hypothesis (Ha) readsthe frequency of reading newspapers significantly affect the ability to understand the discourse of class X SMA Methodist 8 Medan Year 2009/2010 Learning acceptable.Keywords : frequency of reading, newspaper, understand discourse